1712. Epidemiology, Clinical Characteristics, and Outcomes of Influenza-Associated Hospitalizations in Children in the post-2009 Pandemic Era. (31st December 2020) - Kamidani, Satoshi; Garg, Shikha; Campbell, Angela P; Cummings, Charisse N; Openo, Kyle P; McMullen, Chelsea L; Chai, Shua; Herlihy, Rachel; Yousey-Hindes, Kim; Monroe, Maya; Kim, Sue; Lynfield, Ruth; et al.
Abstract: Background: Significant changes in influenza vaccination coverage and antiviral treatment guidance occurred following the 2009 influenza pandemic in children. However, data are limited describing recent epidemiology, clinical characteristics, antiviral use, vaccine coverage, and outcomes of influenza-related hospitalizations in children. Methods: Children < 18 years hospitalized with influenza during seasons 2010–2011 through 2018–2019 were included through the US Influenza Hospitalization Surveillance Network (FluSurv-NET). Age-stratified hospitalization rates were calculated using the number of catchment-area residents with laboratory-confirmed influenza within 14 days prior to or ≤3 days after hospital admission during October 1-April 30 of each influenza season. Data on underlying medical history, influenza vaccination, antiviral use, and outcomes were abstracted from medical records using standard case report forms by trained surveillance officers. Results: Over 9 seasons, 13, 235 children were identified. Stepwise decreases in unadjusted hospitalization rates with age occurred, with the highest rates in infants < 6 months (ranging 56–184 per 100, 000 persons) (Fig.1). Among these children, 56% were male, 34% were non-Hispanic White, 55% had a preexisting medical condition, and 8% were immunocompromised (Table 1). Use of antiviral treatment substantially increased from 56% to 85%, and influenza vaccination rates among hospitalized children increased from 34% to 43% over time. Regarding severe outcomes, 2, 676 (20%) were admitted to ICU, 2, 262 (17%) had pneumonia, 690 (5%) required mechanical ventilation, and 72 (0.5%) died. In univariable analysis, compared to hospitalized infants < 6 months, children >13 years had higher odds of ICU admission (odds ratio (OR), 2.0; 95% CI, 1.7–2.4), mechanical ventilation (OR, 1.7; 95% CI, 1.2–2.3), and pneumonia (OR, 2.6; 95% CI, 2.1–3.3) (Table 2). Figure 1 Table 1 Table 2 Conclusion: Although influenza-related hospitalization rates decreased with increasing age, severe outcomes were more common among hospitalized older children. Room for improvement exists in influenza vaccination coverage and antiviral use. While 20% of children were admitted to ICU, death was uncommon. Disclosures: Sue Kim, MPH, Council of State and Territorial Epidemiologists (CSTE) (Grant/Research Support) Melissa Sutton, MD, MPH, CDC funding (Emerging Infections Program) (Grant/Research Support) Evan J. Anderson, MD, Sanofi Pasteur (Scientific Research Study Investigator)